Dampak Pembangunan Perumahan terhadap Tingkat Pendapatan, Jenis Pekerjaan, dan Fasilitas Publik di Desa Kekeri Kecamatan Gunung Sari Kabupaten Lombok Barat - Kahfi, Arya Ashabul; Firmansyah, M.; Fadli, Muhammad Dzul (TSAQOFAH, 2025)
Development is an ongoing historical process that reflects the dynamics of human civilization, one manifestation of which is housing development—a sector with significant impacts, particularly in peri-urban buffer zones that emerge in response to urbanization and land scarcity in city centers. Kekeri Village, located in Gunung Sari District, West Lombok Regency, exemplifies such an area experiencing rapid residential growth due to its strategic location and proximity to Mataram City. This study aims to analyze the impact of housing development on the socio-economic transformation of the local community, focusing on three key indicators: income levels, types of employment, and the availability of public facilities before and after development. A quantitative descriptive method with a case study approach was employed. The results reveal significant changes in the employment structure, increased economic opportunities, and improved public infrastructure supporting daily activities. These findings indicate that housing development in semi-urban areas has a positive impact on the socio-economic dynamics of local communities. Therefore, inclusive and sustainable development planning is essential to ensure that the benefits of development are distributed equitably.